Factors influencing decision-making power regarding reproductive health and rights among married women in Mettu rural district, south-west, Ethiopia - Afework Tadele; Amanuel Tesfay; Alemi Kebede (BMC, 2019)
Abstract Background Women's decision-making power regarding reproductive health and rights (RHR) was the central component to achieve reproductive well-being. Literatures agree that a women having higher domestic decision-making power regarding their health care were more likely to utilize health services. More than 80% of women in Ethiopia reside in rural areas where they considered as the subordinates of their husbands. This would restrict women to fully exercise their RHR. Thus, this study aims to determine the factors influencing the women's decision-making power regarding RHR in Mettu rural district, South West Ethiopia. Methods A community based cross-sectional study was done among 415 by using randomly selected married women of reproductive age from March to April 2017. Data was entered by using Epi-data manger 1.4 and analyzed by SPSS version 21. Descriptive and multivariate logistic regression analysis was carried out. Result One hundred sixty-eight (41.5%) of the women had greater decision-making power regarding RHR. Woman's primary education AOR 2.62[95% C. I 1.15, 5.97], secondary (9+) education AOR 3.18[95% C. I 1.16, 8.73] and husband's primary education AOR 4.0[95% C. I 1.53, 10.42], secondary (9+) education AOR 3.95 [95% C. I 1.38, 11.26], being knowledgeable about RHR AOR 3.57 [95% C. I 1.58, 8.09], marriage duration of more than 10 years AOR 2.95 [95% C. I 1.19, 7.26], access to micro-credit enterprises AOR 4.26[95% C. I 2.06, 8.80], having gender equitable attitude AOR 6.38 [95% C. I 2.52, 12.45] and good qualities of spousal relation AOR 2.95 [95% C. I 1.30, 6.64] were positively influencing women's decision-making power regarding RHR. Conclusion More than four in ten rural women had greater decision-making power regarding RHR. External pressures (qualities of spousal relation, gender equitable attitude) and knowledge about RHR were found to influence women's decision-making power. Public health interventions targeting women's RHR should take into account strengthening rural micro-credit enterprises, qualities of spousal relations and priority should be given to women with no formal education of husband or herself and marriage duration of < 5 years.